2010
DOI: 10.2172/1034595
|View full text |Cite
|
Sign up to set email alerts
|

Operations & Maintenance Best Practices - A Guide to Achieving Operational Efficiency (Release 3)

Abstract: The mission of FEMP is to facilitate the Federal Government's implementation of sound, costeffective energy management and investment practices to enhance the nation's energy security and environmental stewardship. Each of these activities is directly related to achieving requirements set forth in:• The Energy Policy Act of 2005, which established a number of energy and water management goals for Federal facilities and fleets and also amended portions of the National Energy Conservation Policy Act (NECPA).• Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 2 publications
0
33
0
14
Order By: Relevance
“…1 Facilities management: (a) facilities manager locating utility on a paper map and (b) facilities manager's maintenance cart and equipment maintenance, which is to wait until a utility breaks before it is serviced (Sullivan et al 2010). The most cost effective maintenance is preventative, in which actions are performed on a time-based schedule with the aim of sustaining or extending a resource's useful life through controlling degradation to an acceptable level (Sullivan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1 Facilities management: (a) facilities manager locating utility on a paper map and (b) facilities manager's maintenance cart and equipment maintenance, which is to wait until a utility breaks before it is serviced (Sullivan et al 2010). The most cost effective maintenance is preventative, in which actions are performed on a time-based schedule with the aim of sustaining or extending a resource's useful life through controlling degradation to an acceptable level (Sullivan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A Department of Energy study indicated 35 percent reductions in equipment downtime, 70 percent fewer equipment breakdowns, and 25 percent lower maintenance costs could be achieved through a best practices remote monitoring and predictive maintenance program. 3 For OEMs, providing remote diagnostic M&D services for customers can create new, recurring revenue streams. However, in many cases, it is not entirely clear where the value can be captured by the OEM through a remote M&D service.…”
Section: Notesmentioning
confidence: 99%
“…Usually, corrective maintenance is an unscheduled maintenance action, basically composed of unpredictable maintenance needs that cannot be preplanned [25]. Shorting the life time of asset and increased repairing labour cost are major drawbacks of corrective maintenance [26]. Time based maintenance action is performed on the asset at a scheduled time regardless of its actual condition [27].…”
Section: Asset Management Techniquesmentioning
confidence: 99%